Cuidando a paciente con síndrome de Stevens Johnson: a propósito de un caso - Gia Morocho, Tatiana Juleysi; Chamba Suarez, Flor Talia (My University, 2024)
Stevens-Johnson Syndrome (SJS) is a severe dermatological disease characterized by epidermal necrolysis and mucosal involvement, usually induced by drugs or infections. Objective: To provide nursing care to a patient with Stevens-Johnson Syndrome (SJS) in order to improve their health and restore the skin integrity caused by the disease. Methodology: A descriptive, observational, and qualitative study was conducted. It analyzed the case of a 28-year-old patient who was admitted to the hospital with a local skin infection that progressed to SJS, maculopapular lesions, mucosal erosions, and ocular involvement. Comprehensive management was implemented, including intravenous hydration, analgesia, antibiotics, antivirals, and dermatological care, resulting in a favorable clinical outcome. From a nursing perspective, care plans were implemented in SOAPIE format, prioritizing pain management and infection prevention. To structure the interventions, the NANDA-NIC-NOC taxonomy was used, identifying two key nursing diagnoses: acute pain (NANDA 00282) and risk of infection (NANDA 00004). Strategies implemented included administration of analgesics, protective dressings, relaxation techniques, antibiotics, and sterile dressings, reducing pain perception from 8/10 to 4/10 and preventing secondary infections. Hospital outcomes demonstrated the importance of early diagnosis and a multidisciplinary approach to minimize complications and improve prognosis. It is concluded that Stevens-Johnson syndrome requires timely and coordinated treatment and outpatient follow-up to avoid long-term sequelae. It is essential to strengthen the training of healthcare personnel in the recognition and management of this condition, as well as to optimize care protocols based on scientific evidence.
El Síndrome de Stevens-Johnson (SSJ) enfermedad dermatológica grave caracterizada por necrólisis epidérmica y afectación mucosa, generalmente inducida por fármacos o infecciones. Objetivo: Aplicar cuidados de enfermería en un paciente con Síndrome de Steven Johnson con el fin mejorar su condición de salud y recuperar la integridad cutánea causada por la enfermedad. Metodología: estudio descriptivo, observacional y cualitativo; analizó el caso de un paciente de 28 años que ingresó al hospital con infección local de la piel, evolucionando a SSJ, lesiones maculopapulares, erosiones en mucosas y compromiso ocular. Se implementó un manejo integral hidratación intravenosa, analgesia, antibióticos, antivirales y cuidados dermatológicos, obteniendo una evolución clínica favorable. Desde el enfoque de enfermería, se aplicaron planes de cuidados en formato SOAPIE, priorizando el manejo del dolor y la prevención de infecciones. Para estructurar las intervenciones, se utilizó la taxonomía NANDA-NIC-NOC, identificando dos diagnósticos de enfermería clave: dolor agudo(NANDA 00282) y riesgo de infección (NANDA 00004). Se implementaron estrategias: administración de analgésicos, apósitos protectores, técnicas de relajación, antibióticos y curaciones estériles, logrando reducir la percepción del dolor de 8/10 a 4/10 y prevenir infecciones secundarias. La evolución hospitalaria demostró la importancia del diagnóstico temprano, un abordaje multidisciplinario para minimizar complicaciones y mejorar el pronóstico. Se concluye que el síndrome de Stevens-Johnson, requiere un tratamiento oportuno y coordinado, seguimiento ambulatorio para evitar secuelas a largo plazo. Es esencial fortalecer la capacitación del personal de salud en el reconocimiento y manejo de esta patología, así como optimizar los protocolos de atención basados en evidencia científica.
Keywords: SINDROME DE STEVENS JOHNSON; CUIDADOS DE ENFERMERÍA; MANEJO HOSPITALARIO; DIAGNOSTICOS DE ENFERMERÍA